DESIGN AND DEVELOPMENT OF AN EDUCATIONAL DIGITAL GAME BASED ON MATHEMATICS COURSE TRANSFORMATION GEOMETRY - Mustafa NAVRUZ; Şakir TAŞDEMIR (International Journal of Applied Methods in Electronics and Computers, 2019)
The digital gaming industry is growing rapidly both economically and in terms of the masses it is influencing. This growth in the sector makes digital games effective in culture and education. In order to use this effect in a beneficial way, it is necessary to be included in the sector. In this research, 8th grade mathematics curriculum a game called “Simetri” has been developed for the purpose of reinforcing the acquisitions of the transformation Geometry subject. The works and processes performed during the development are discussed in this article. The basic structure of the game; it is based on the process of automatically generating the image after the correct clicking of the corners of the image which will result from the reflection of the polygons drawn on the squared paper, dot paper and the coordinate plane with respect to the determined axis of symmetry. There are different difficulty stages within the game and separate levels within these stages. There is also a scoring system in the game and new records are kept. Although the game is mainly based on the concept of reflection, it is open to further development of the concept of translation and the solution of more complex problems.